ANALISIS PENGGUNAAN Z-Score ALTMAN UNTUK MEMPREDIKSI TINGKAT KEBANGKRUTAN PADA INDUSTRI TELEKOMUNIKASI DI BURSA EFEK INDONESIA PERIODE 2007-2010. - Hana Tamara Putri (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
The Background of this research is to know and to analize prediction of company bankruptcy of Telecommunication Industry in BEI periods 2007-2010 which focuses object are four companies which have all criteria in analysis by method Z-score Altman. As we know, the goal of company is not being bankrupt so that the company needed a method to predict the bankruptcy as soon as possible. One of the method is Z-Score Altman, this method used to analize financial statements. Goal this research is to know the potential of bankruptcy, rate of bankruptcy, and insolvensy ranking  of Telecommunication Industry in BEI periods 2007-2010.Four companies taken as object is PT. XL Axiata, Tbk (eks PT. Excelcomindo, Tbk), PT. Mobile-8 Telecom, Tbk, PT. Indosat, Tbk and PT. Telekomunikasi Indonesia (PERSERO), Tbk is analyze by using financial statements taken away from by the year 2007 to 2010. After that calculated values of variable x1 to variable x5 and next calculated the value of each variable into Altman’s Formula to produce the score ( Z-Score). Determining the Z-Score with this categories :a)     Z-Score < 1,20 are on potential bankruptcy categoryb)    1,20 < Z-Score < 2,90 are on grey area categoryc)     Z-Score > 2,90 are on non bankruptcy companyKeywords : financial distress, bankruptcy, telecommunication industry.